One-on-one meeting with the winners of the Zambia accelerator program: report - Annaiah, A (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
The AICCRA (Accelerating Impacts of CGIAR Climate Research for Africa) project promotes climate-smart agriculture in Africa by leveraging cutting-edge research from CGIAR, the world’s largest publicly funded research network for food security. The initiative enhances access to climate information services (CIS) and climate-smart agriculture (CSA) technologies to build a resilient agrifood sector. On June 21, 2024, AICCRA Zambia launched the second cohort of its Agribusiness Accelerator Program in Lusaka, Zambia, aimed at supporting SMEs in the agribusiness sector. Following an extensive screening process, three agribusinesses were chosen as winners on January 27, 2025. To further assist these accelerator winners, the CGIAR ILRI Digital Innovation (DI) initiative conducted virtual one-on-one meetings on February 5th & 6th, 2025, offering digital services and innovations tailored to their businesses. By integrating digital solutions, these agribusiness SMEs can scale their impact, enhance profitability, and strengthen their role in food security and climate resilience.